Morphology, rheology, and physical properties of polymer-modified asphalt binders - Behnood, Ali; Modiri Gharehveran, Mahsa (European polymer journal, 2019)
[Display omitted] •Polymers can be used to improve the physical and rheological properties of asphalt binders.•Polymer modification requires further investigation especially regarding the low temperature properties.•Factors affecting the properties of polymer-modified asphalt binders (PMAs) are reviewed.•Recently developed techniques to enhance the properties of PMAs are reviewed. Asphalt binders play an integral role in the performance and properties of asphalt mixtures. Increased traffic-related factors on the roadways such as heavier loads, higher traffic volume, and higher tire pressure combined with substantial variation in daily and seasonal temperatures of the pavement have been responsible for the asphalt pavements failure. To prevent or mitigate these failures, many attempts have been made by polymer scientists and civil engineers to improve the performance of asphalt pavements by modifying the properties of asphalt binders. A good modifier changes the failure properties such that binder yields more stresses and strains before failure. Modification of asphalt binders through the addition of a polymer to improve their rheological and physical properties has a long history in asphalt industry. Once the polymer is properly mixed with the asphalt binder, a swallowed polymer network is formed, which contributes to the changes in viscoelastic behavior. However, polymer-modified asphalt binders may have some drawbacks related to the poor solubility of polymers. Understanding the internal structure of polymer-modified asphalt binders has been the subject of numerous research studies. Available studies regarding the affecting parameters on the properties of the polymer-modified asphalt binders are reviewed here. Various types of polymers used in asphalt industry and their effects on the rheological, morphological, physical and mechanical properties of polymer-modified asphalt binders are also discussed in this paper. In addition, this paper provides a review on the techniques used to overcome/mitigate the shortcomings of conventional polymer-modified asphalt binders.